Upper extremity morbidity after radial forearm flap harvest: a prospective study. (February 2014) - Fang, Qi-Gen; Shi, Shuang; Zhang, Xu; Li, Zhen-Ning; Liu, Fa-Yu; Sun, Chang-Fu
Objective: To determine the effect of radial forearm free (RFF) flap harvest on patient-reported postoperative upper extremity disability. Methods: Patients undergoing RFF flap reconstruction following resection of head and neck cancer were recruited and matched with similar patients undergoing non-RFF reconstruction. All subjects completed the Disability of the Arm, Shoulder, and Hand (DASH) questionnaire preoperatively and at least 1 year postoperatively. Results: Postoperative DASH scores were significantly higher (more severe disability) in patients undergoing RFF flap reconstruction (6.93 ± 5.54; n = 52) compared with those undergoing non-RFF flap surgeries (2.95 ± 4.42; n = 52). Preoperative DASH score, flap size, patient age and tumour stage were significantly correlated with postoperative DASH score. Conclusion: Excluding the effect of neck dissection, RFF flap reconstruction has a significant deleterious effect on upper extremity function.